Awake Video-Assisted Thoracoscopic Surgery with Erector Spinae Plane Block - ZENGİN, SENİYYE ÜLGEN; ORHON ERGÜN, MELİHA; LAÇİN, TUNÇ (My University, 2022)
Erector spinae plane block has been used for postoperative pain following thoracic surgery as an alternative to epidural block or adjunct to general anesthesia in thoracic procedures. However, its sole use during thoracoscopic surgery without general anesthesia is rare. Here, we report two cases in which erector spinae plane block was successfully used as the only anesthetic method during video-assisted thoracoscopy.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Medicine; Health Sciences; Surgery Medicine Sciences; CERRAHİ; Klinik Tıp; Klinik Tıp (MED); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); Cerrahi; Surgery; Erector spinae plain block (ESPB); Video-assisted thoracic surgery (VATS); Awake anesthesia; PARAVERTEBRAL BLOCK; ANESTHESIA